A FEMINIST STYLISTICS ANALYSIS IN RUPI KAUR’S THE SUN AND HER FLOWERS - Saskia Febiola Siregar; Eddy Setia; Siamir Marulafau (Universitas Islam Sumatera Utara, 2020)
This research was aimed at analyzing linguistic stylistics describing how women and men presented in texts by applying a feminist approach, i.e. feminist stylistics. This research focuses not only on stylistics analysis that considers linguistic structure and how it affects society, but also on how the position of women as actors, as well as the position of ideas or events presented in the text. This research used a qualitative method. The words, phrases or sentences, and discourses reflecting gender-specific in the novel become the data of the research. The researchers use Mills' feminist stylistics theory to analyze the data. In this study, there are several tendencies of women or men associated with the text. In a collection of poems, it is often found several italics at the bottom, and it is to emphasize the topic of the poem concerned. This research shows that Rupi Kaur, as the author, seems to want readers to understand his poetry as much as what he wrote and wanted. In addition, this study found that gender-specific terms are mostly used to refer primarily to female gender.